2015
DOI: 10.1371/journal.pone.0120515
|View full text |Cite
|
Sign up to set email alerts
|

1α,25-Dihydroxyvitamin D3 Induces Neutrophil Apoptosis through the p38 MAPK Signaling Pathway in Chronic Obstructive Pulmonary Disease Patients

Abstract: BackgroundReduced neutrophil apoptosis plays an important role in the pathogenesis of acute exacerbation chronic obstructive pulmonary disease (AECOPD). The p38 mitogen-activated protein kinase (MAPK) signaling pathway is involved in neutrophil apoptosis. 1α,25-Dihydroxyvitamin D3 (1α,25VitD3) can induce tumor cell apoptosis. The aim of this study was to assess the effects of 1α,25VitD3 on peripheral blood neutrophil apoptosis in AECOPD and examine the role of the p38 MAPK signaling pathway.MethodsThe study en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 24 publications
0
15
0
Order By: Relevance
“…1,25 (OH) 2 D did not show any effect on the phagocytic capacity of these macrophages but it increased the levels of cathelicidin [36]. Furthermore, in venous blood samples, the rate of peripheral blood neutrophilic apoptosis in patients with acute exacerbations of COPD was slower than in healthy controls and this neutrophilic apoptosis is increased after administration of vitamin D through the p38MAPK pathway [91]. Taken together, even though in a controlled setting of cell culture, these data clearly show that vitamin D has potential to interfere with the immune reaction in response to a respiratory infection in COPD.…”
Section: Vitamin D In Copd and Exacerbationsmentioning
confidence: 84%
“…1,25 (OH) 2 D did not show any effect on the phagocytic capacity of these macrophages but it increased the levels of cathelicidin [36]. Furthermore, in venous blood samples, the rate of peripheral blood neutrophilic apoptosis in patients with acute exacerbations of COPD was slower than in healthy controls and this neutrophilic apoptosis is increased after administration of vitamin D through the p38MAPK pathway [91]. Taken together, even though in a controlled setting of cell culture, these data clearly show that vitamin D has potential to interfere with the immune reaction in response to a respiratory infection in COPD.…”
Section: Vitamin D In Copd and Exacerbationsmentioning
confidence: 84%
“…When neutrophil has hyperactivity in metabolism due to various factors, the metabolites including ROS radical group rises and cause inflammatory injuries in airway and lung tissues [20,21]. In studies investigating the relationship between neutrophil apoptosis delay and pathogenesis of COPD, it was found that aberrant protein expression of apoptosis family is one of the key reasons for neutrophil apoptosis [22,23]. The CFTR chloride ion serves a critical role in apoptosis through regulating the levels of ROS and GSH [24,25].…”
Section: Discussionmentioning
confidence: 99%
“…Yang et al showed that the level of phospho-p38 MAPK was increased in peripheral blood neutrophils of acute exacerbation of COPD patients. 40 Li et al demonstrated that the ERK/p38 MAPK pathway was enhanced in CSE-induced HBE cells. 41 Li et al indicated that the phosphorylation of ERK and p38 was increased in mice exposed to cigarette smoke.…”
Section: Discussionmentioning
confidence: 99%